The Correlation between miRNA and Lymph Node Metastasis in Gastric Cancer. - Huang, Kuo-Hung; Lan, Yuan-Tzu; Fang, Wen-Liang; Chen, Jen-Hao; Lo, Su-Shun; Li, Anna Fen-Yau; Chiou, Shih-Hwa; Wu, Chew-Wun; Shyr, Yi-Ming (BioMed Research International, 2015)
Lymph node metastasis (LNM) in gastric cancer is associated with higher rate of cancer recurrence and poor prognosis. As a result, a reliable biomarker for the prediction of LNM is important and would be valuable in the clinical practice. MiRNA microarray revealed that ten miRNAs were expressed significantly different among patients with or without LNM. A total of 46 gastric cancer patients were enrolled and divided into two groups (23 in each group) according to the presence or absence of LNM. RT-PCR of these 10 miRNAs was investigated and compared between the two groups. MiR-1207-5p was significantly upregulated in gastric cancer patients without LNM compared with those with LNM. Patients with upregulated miR-1207-5p had less scirrhous stromal reaction, less lymphovascular invasion, and earlier pathological T category, N category, and TNM stage, compared with those with downregulated or unchanged miR-1207-5p. Multivariate analysis showed that stromal reaction type, lymphovascular invasion, pathological T category and TNM stage, and expression of miR-1207-5p were independent risk factors of LNM. MiR-1207-5p could serve as a useful biomarker in the prediction of LNM in gastric cancer.